A study on preferred houses in Kubang Pasu: Undergraduates' students in UUM - Mohd Nor, Fatin Amira; Pang, Sia Yen; Omar, Ahmad Syahir; Ruzi, Noruzieyana; Wang, Mei Yin; Ahmad, Azhar (2015)
Identifying customer preferences in order to achieve high business performance in view of future customers‟ satisfaction in housing offerings is critically important.For that, this research aims to evaluate the alignment between customer preferences, housing affordability and housing promotions among undergraduates‟ students in UUM. The main issues covered are price, financial assistance and customer satisfaction in housing sector.Besides using a survey to gather customer perceptions, this research also employs key stakeholders' perspectives into the analysis.It is expected that the findings could contribute towards greater understanding in view of customer behavior in the local housing development's market.This research is also expected to provide good insights on managerial applications.